2015
DOI: 10.1161/strokeaha.114.008407
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of a Clinically Relevant Stroke Model

Abstract: 18F]-2-fluoro-2-deoxy-d-glucose positron emission tomography or magnetic resonance imaging during 90-minute occlusion of the middle cerebral artery and during 60 minutes after reperfusion. Results were correlated to magnetic resonance imaging of cerebral blood flow, diffusion of water, lactate formation, and histological data on cell death and blood-brain barrier breakdown. Results-We detected an increased [2-18 F]-2-fluoro-2-deoxy-d-glucose uptake within ischemic regions succumbing to infarction and in the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Selective M2 occlusion preserves collateral blood flow to the MCA from the anterior (ACA) and the posterior cerebral arteries (PCA), thereby producing ischemic lesions closer in relative size and with a regional blood flow situation similar to those commonly found in patients [10, 12]. The aim of this study was to use the M2CAO model to provide a clinically relevant profile of the emergence of ischemic injury in such cases.…”
Section: Introductionmentioning
confidence: 99%
“…Selective M2 occlusion preserves collateral blood flow to the MCA from the anterior (ACA) and the posterior cerebral arteries (PCA), thereby producing ischemic lesions closer in relative size and with a regional blood flow situation similar to those commonly found in patients [10, 12]. The aim of this study was to use the M2CAO model to provide a clinically relevant profile of the emergence of ischemic injury in such cases.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced gene or protein expression of both GLUT1 and SGLT1 at the BBB has been implicated in experimental models of ischemic stroke and TBI [ 231 , 233 , 234 ]. Consistent with these findings, brain imaging studies have suggested elevated glucose uptake and glucose hypermetabolism during ischemic stroke, especially in peri-infarcted regions [ 234 , 235 ]. Due to the high abundance of GLUTs at the BBB, they are thought to represent a major route for transendothelial water flux during ionic edema, as they have the ability to passively transport water, analogously to the AQPs [ 13 , 14 ].…”
Section: Glucose Transporters (Gluts)mentioning
confidence: 57%
“…Diffusion-weighted magnetic resonance imaging (MRI) has been shown to be an acceptable measure for infarct core volume [19,20] and can be used to ascertain treatment effects. Other advanced imaging modalities such as permeability imaging [21], positron emission tomography [22], thrombus imaging [23], and diffusion tensor imaging [24] can provide critical information on specific intervention targets. Finally, detailed histopathologic analyses can confirm postulated improvements, imaging findings, or safety in animal studies.…”
Section: Going Beyond Functional Endpointsmentioning
confidence: 99%